Side specific effect of 5-hydroxytryptamine on NaCl transport in the apical and basolateral membrane of rat tracheal epithelia - Nam, B. D; H. J., Park (Physiological research, 2006)
5-Hydroxytryptamine (5-HT) can be released from mast cells and platelets through an IgE-dependent mechanism and may play a role in the pathogenesis of allergic bronchoconstriction. However, the effect of 5-HT on ion transport by the airway epithelium is still controversial. The objective of this study was to determine whether 5-hydroxytryptamine (5-HT) regulates NaCl transport by different mechanisms in the apical and basolateral membrane of tracheal epithelia. We studied the rat tracheal epithelium under short-circuit conditions in vitro. Short-circuit current (Isc) was measured in rat tracheal epithelial monolayers cultured on porous filters. 5-HT inhibited Na+ absorption [measured via Na+ short-circuit current (INasc)] in the apical membrane and stimulated Cl- secretion [measured via Cl- short-circuit current (IClsc)] in the basolateral membrane. Functional localization using selective 5-HT agonists and antagonists suggest that IClsc is stimulated by the basolateral membrane-resident 5-HT receptors, whereas INasc is inhibited by the apical membrane-resident 5-HT2 receptors. The basolateral addition of 5-HT increases intracellular cAMP content, but its apical addition does not. The addition of BAPTA/AM blocked the decrease of INasc which was induced by the apical addition of 5-HT, and 5-HT increased intracellular Ca concentrations. These results indicate that 5-HT differentially affects INasc and IClsc across rat tracheal monolayers through interactions with distinct receptors in the apical and the basolateral membrane. These effects may result in an increase of water movement towards the airway lumen.
Keywords: mastocyty; Sodium Chloride; Animals; Mast Cells; Serotonin; chlorid sodný; trombocyty; Trachea; serotonin; Epithelial Cells; Immunoglobulin E; trachea; Blood Platelets; Rats, Sprague-Dawley; iontové kanály; bronchospasmus; Ion Channels; potkani Sprague-Dawley; Bronchial Spasm; imunoglobulin E; zvířata; epitelové buňky